2016
DOI: 10.4103/1450-1147.174698
|View full text |Cite
|
Sign up to set email alerts
|

18F-sodium fluoride PET-CT hybrid imaging of the lumbar facet joints: Tracer uptake and degree of correlation to CT-graded arthropathy

Abstract: We aim to evaluate 18F-NaF uptake by facet joints with hybrid PET-CT technique. Specifically, we evaluate NaF uptake in the facet joints of the lower lumbar spine, and correlate with the morphologic grade of facet arthropathy on CT. 30 consecutive patients who underwent standard vertex to toes NaF PET-CT for re-staging of primary neoplastic disease without measurable or documented bony metastases were identified. Maximum (SUVmax) and average (SUVavg) standardized uptake values were calculated for each L3-4, L4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This finding is consistent with a previous study wherein a similarly weak correlation was found between NaF-PET uptake and CT measures of facet arthropathy, further supporting the hypothesis that physiologic information afforded by NaF uptake may supplement conventional structural imaging for identifying symptomatic facet joints. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with a previous study wherein a similarly weak correlation was found between NaF-PET uptake and CT measures of facet arthropathy, further supporting the hypothesis that physiologic information afforded by NaF uptake may supplement conventional structural imaging for identifying symptomatic facet joints. 6 …”
Section: Discussionmentioning
confidence: 99%
“…3–5 The utility of 18 F-NaF PET for evaluating degenerative disease of the lumbar spine remains largely unexplored. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Not only does NaF-PET/CT facilitate the diagnosis of pars stress but it can also help diagnose other potential causes of back pain, such as facet arthropathy. [80][81][82] The observation that NaF uptake at the cervical, thoracic, and lumbar spine is associated with increased body weight in healthy individuals suggests that NaF-PET/CT can detect early changes in the spine related to degeneration. 83 In 42 adult patients with back pain and no history of spine surgery, NaF-PET/CT scans identified the cause of pain in 37 (88%) of the patients.…”
Section: Back Painmentioning
confidence: 99%
“…82 Furthermore, NaF activity at lumbar facet joints has been found to correlate with both MR findings and clinical disability. 80 Mabray and colleagues 81 observed that, in 30 adult patients who underwent imaging by NaF-PET/CT, uptake of NaF was only weakly correlated with CT Pathria grade of facet osteoarthropathy. Thereby, the investigators reasoned that the assessment of bone turnover with NaF provided new information that can be used to supplement structural data provided by CT.…”
Section: Back Painmentioning
confidence: 99%
“…36,40 Additionally, increased F 18 -NaF uptake was shown to correlate well with those patients with facet joint pain. [41][42][43] Further, significantly increased F 18 -NaF PET subchondral bone uptake was observed in a patient population at risk for developing degenerative joint disease. 44 These findings support the hypothesis that increased metabolic bone activity detected with F 18 -NaF PET can serve as a marker for early bone remodeling in OA.…”
Section: F 18 -Sodium Fluoride Pet/mri For Osteoarthritismentioning
confidence: 99%